The use of protein as a carrier of methotrexate for experimental cancer chemotherapy. III. Human serum albumin-methotrexate derivative, its preparation and basic testing - Bures, L; Bostík, J; Motycka, K; Spundová, M; Rehák, L (Neoplasma, 1988)
The preparation and a more detailed characterization of human serum albumin-methotrexate derivative (HSA-MTX) is described. The synthesis of the derivative was performed by means of 1-ethyl-3-(3'-dimethylaminopropyl)-carbodiimide (in methoiodide form) (WSC). Results of many experiments showed that, on the average, about 26 molecules of methotrexate (MTX) were coupled to one molecule of human serum albumin (HSA). The relative molecular weight of the formed derivative was estimated by gel chromatography on Sepharose 6B or on high-pressure liquid chromatography (HPLC) on SWK column, respectively. From the obtained data it follows that a considerable part of the HSA-MTX derivative formed protein-protein conjugate (up to about 4 X Mr HSA), nevertheless the derivative retains its good solubility as a native albumin. In order to eliminate the possibility of influencing the cytostatic activity of the derivative with byproducts of its synthesis, human serum albumin-folic acid derivative (HSA-FA) was prepared and tested by the same method. All demonstrated experiments proved that MTX was the only compound possessing the cytostatic activity. During the experimental therapy of Gardner lymphosarcoma (LSG) the following was found: (1) The intratumorous application of the drug was the most effective way of administration. (2) Any type of administration of the HSA-MTX derivative exerted a better effect than the same way of administration of free MTX. (3) The comparison of two (repeated) administrations of both drugs showed clearly that the HSA-MTX derivative was more efficient than free MTX. After HSA-MTX derivative treatment all animals survived without tumor. (4) For the estimation of the toxicity of the HSA-MTX derivative, three times and five times repeated intraperitoneal administration was performed. It was concluded that although the derivative was more toxic than free MTX, its therapeutic activity was better. After the elimination of the toxic manifestation of the HSA-MTX derivative by a suitable arrangement of drug doses, five times higher efficacy of the derivative was reached, as compared with free MTX. (5) The therapy by the HSA-FA derivative did not exhibit any therapeutic effect. The reason why HSA was used as a macromolecular carrier for cytostatics is discussed.
Keywords: methotrexát; sérový albumin; Drug Evaluation, Preclinical; nosiče léků; preklinické hodnocení léčiv; Methotrexate; statistika jako téma; nehodgkinský lymfom; Serum Albumin; zvířata; kyselina listová; Mice; Statistics as Topic; Drug Carriers; myši; Lymphoma, Non-Hodgkin; Animals; Folic Acid